Donation based Crowd Funding Reviewed from The Sadd Adz-Dzari'ah Perspective - Syaifuddin Zuhdi; Sarah Camila Octavian (Proceeding International Conference Restructuring and Transforming Law, 2023)
Uncertainty regarding regulations regarding the implementation of donation-based crowdfunding in Indonesia has resulted in a weak supervisory function carried out by the Ministry of Social Affairs. so this creates the potential for misappropriation of funds, donation fraud, money laundering and other criminal acts. Sadd Dzari'ah as a method of preventing harm is used to weigh the level of harm in implementing donation based crowdfunding. The aim of this research is to find out what the concept of donation based crowdfunding is in Indonesia, and how the legal status of donation based crowdfunding is viewed from a sadd dzari'ah perspective. The research method used is normative, the type of research is descriptive qualitative, and the data collection method is a literature study of legal and non-legal materials regarding donation based crowdfunding obtained by reading, viewing, listening or searching. The result of this research is to prohibit the implementation of donation-based crowdfunding based on Sadd Dzari'ah's analysis that eliminating harm takes priority over taking benefits.